Evaluation of nitrogen fixation in bean ( Phaseolus vulgaris) - Ruschel, Alaídes Puppin; Ruschel, Renato (Pesquisa Agropecuaria Brasileira, 2014)
Rates of nitrogen fixation by 2 bean varieties, Rico 23 and Preto 143, grown in soils in the greenhouse, were determined 35, 50 and 65 days after planting using the acetylene reduction method as a measure of nitrogenase activity and by measuring total nitrogen and plant dry weight. Changes in nodulation were followed by measuring nodule numbers and dry weights of nodules. Nodule mass was effected by variety, Preto 143 increasing nodule number linearly. However, nodule weight decreased in plants older than 50 days. Inoculation with Rhizobium phaseoli increased weight and total nitrogen of bean plants, denoting a protein increase in the plant as a result of fixation. It was demonstrated that symbiotic nitrogen fixation caused an increase in dry weight of 65 - day - old plants and an increase in the total nitrogen level of above ground plant parts in 50- day - old plants. Acetylene reduction measurements were good estimations of nitrogen fixation in beans. A conversion factor of two (2) was determined relating ethylene moles to dinitrogen moles fixed, under the conditions of this experiment.